Effects of zeolite and liquid urea on growth of black pepper (Piper nigrum L.) - Bundan, Latip (2012)
Ammonia volatilization is one of the major problems which leads to poor urea-N use efficiency. When urea is applied to the soil, it temporarily raises soil pH and hence causes ammonia volatilization. Ammonia loss is associated with soil properties such as pH and CEC. As black pepper is known for high nutrient demand, fertilizer use efficiency and frequency need consideration in its cultivation. Thus, proper fertilizer management is essential for improving the effectiveness of fertilizers particularly N. An approach of increasing CEC that leads to improvement of soil NH4 + and reduction of ammonia volatilization is promising. Therefore, this study was carried out to minimize ammonia volatilization from urea at different levels of zeolite and to improve urea-N use efficiency by mixing urea with zeolite. For the incubation study, five treatments were evaluated using close-dynamic air flow system method, arranged in a completely randomized design. Treatments evaluated were: (T0) soil alone, (T1) 2.60 g granular urea, (T2) 2.60 g liquid urea, (T3) 2.60 g liquid urea + 4 g of zeolite, (T4) 2.60 g liquid urea + 8 g of zeolite and (T5) 2.60 g liquid urea + 12 g of zeolite. At the end of this study, soil samples were analyzed for pH, exchangeable ammonium (NH4 +) and available nitrate (NO3 -) using standard procedures. When urea was applied in the liquid form, ammonia loss was reduced compared to granular urea but not significantly different among the treatments with and without zeolite. Besides, application of both liquid urea and zeolite was found to increase accumulation of exchangeable ammonium concentration. This could be due to retention of ammonium ions at the exchange sites of zeolite. Hence, soil column experiment under green house condition was conducted to determine the effect of treatments on growth of black pepper. The Kuching variety was used to evaluate the effect of these treatments on N, P and K uptake and their use efficiency including soil inorganic N (exchangeable ammonium and available nitrate), available P, exchangeable K and pH. The treatments evaluated were: (T0) no fertilizer, (T1) 6.52 g granular urea, (T2) 6.52 g liquid urea, (T3) 6.52 g liquid urea + 57.2 g of zeolite, (T4) 6.52 g liquid urea + 114.4 g of zeolite and (T5) 6.52 g liquid urea + 171.6 g of zeolite. Standard requirement for the triple superphosphate and muriate of potash were applied except for T0. The results showed that application of zeolite significantly increased soil available N, P, exchangeable K, Mg and Ca. This is because the ability of zeolite to supply essential secondary elements and to reduce soil cation loss through leaching. The highest amount of zeolite (T5) increased soil pH and it significantly improved leaf chlorophyll content, number of leaves, N, P, and K uptake and their use efficiency. Application of zeolite reduced ammonia loss and increased accumulation of available nutrients for growth of black pepper as well as improving N, P and K uptake and their use efficiency. Hence, application of zeolite could be an alternative way to minimize the use of fertilizer as well as reducing environmental pollution.